Dynamic microwave-assisted extraction combined with liquid phase microextraction based on the solidification of a floating drop for the analysis of organochlorine pesticides in grains followed by GC - Guijie Li; Xu Zhang; Tingting Liu; Hongxiu Fan; Hongcheng Liu; Shangyu Li; Dawei Wang; Lan Ding (Food Science and Human Wellness, 2021)
A convenient, cost-effective and fast method using dynamic microwave-assisted extraction and liquid phase microextraction based on the solidification of a floating drop was proposed to analyze organochlorine pesticides in grains including rice, maize and millet. Twelve samples can be processed simultaneously in the method. During the extraction process, 10% acetonitrile-water solutions containing 110 μL of n-hexadecane were used to extract organochlorine pesticides. Subsequently, 1.0 g sodium chloride was placed in the extract, and then centrifuged and cooled. The n-hexadecane drops containing the analytes were solidified and transferred for determination by gas chromatography-electron capture detector without any further filtration or cleaning process. Limits of detection for organochlorine pesticides were 0.97–1.01 μg/kg and the RSDs were in the range of 2.6%–8.5%. The developed technology has succeeded in analyzing six real grains samples and the recoveries of the organochlorine pesticides were 72.2%–94.3%. Compared with the published extraction methods, the developed method was used to analyze organochlorine pesticides in grains, being more environmentally friendly, which is suitable for the daily determination of organochlorine pesticides.